ECOTEOLOGI SEBAGAI PARADIGMA BARU DAKWAH ISLAM DI ERA KRISIS IKLIM: TELAAH GAGASAN MENTERI AGAMA RI DALAM KONTEKS KEINDONESIAAN - Rohani Rohani; Afriantoni Afriantoni (Journal of Innovative and Creativity, 2026)
Background: The study purpose was to critically examine the emergence of ecotheology as a contemporary paradigm within Islamic preaching in response to the global climate crisis, with particular attention to its formulation and implementation by the Indonesian Ministry of Religious Affairs. This research seeks to reinterpret the Islamic concept of khalifah fi al-ardh by expanding its meaning beyond spiritual stewardship toward concrete ecological responsibility. By positioning environmental awareness as an integral element of religious discourse, the study aims to highlight the transformative role of Islamic preaching in addressing sustainability, ecological justice, and social change in Indonesia. Materials and ethods: This study employed a qualitative descriptive approach using document-based research. Data were collected through systematic analysis of official speeches, policy documents, institutional programs, preacher training modules, and Islamic education curricula issued or endorsed by the Ministry of Religious Affairs. A critical discourse analysis framework was applied to explore how ecotheological narratives are constructed, disseminated, and institutionalized within contemporary Islamic preaching practices. Results: The findings reveal that ecotheology has begun to be operationalized through several initiatives, including environmentally friendly mosque programs, eco-pesantren development, environmental literacy training for preachers, and the integration of ecological themes into Islamic education. Despite ongoing structural and cultural challenges, these initiatives demonstrate a gradual shift toward more contextual, practical, and environmentally responsive forms of Islamic preaching. Conclusion: This study concludes that ecotheology represents a significant conceptual and practical transformation in Islamic preaching in Indonesia. By aligning spiritual teachings with environmental responsibility, this paradigm offers a strategic framework for religious engagement with climate-related challenges and contributes to broader efforts toward sustainable and socially responsible religious practices.